2022
DOI: 10.1002/ejic.202200677
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐Polarity‐Induced Assembly of Calixarene‐Capped Titanium‐Oxo Clusters with Catalytic Activity in the Oxygenation of Sulfides

Abstract: Four calixarene-coordinated titanium-oxo clusters, namely, [Ti 4 (C6A) 2 (μ 3 -O) 2 (DMF) 2 ] (CIAC-258), [Ti 8 (H 3 C6A) 4 (C 6 H 5 PO 3 ) 8 (μ 2 -O) 4 ] 4À (CIAC-259), [Ti 6 (TC4A) 3 (μ 2 -O) 3 (OiPr) 6 ] (CIAC-260) and [Ti 6 (H 2 TC4A) 4 (C 6 H 5 PO 3 ) 4 (μ 2 -O) 5 (DMF) 2 ] 2À (CIAC-261) were obtained, which feature sandwich-like, windmill-like, triangular, and tetrahedral structures, respectively. The polarity of the solvent determines the involvement of the auxiliary ligand phenylphosphonic acid in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The potential catalytic pathways are discussed as follows. Numerous studies have demonstrated that the Ti–peroxo species, formed by the combination of the Ti active site and H 2 O 2 , are responsible for the catalytic oxidation process. , As illustrated in the stacking diagram of the Ti 2 -SA cluster (Figure S5), a substantial number of Ti-OR units are extended outside rather than encapsulated by the calixarene. The labile −OR groups on the cluster surface can dissociate and expose the active Ti 4+ ions, which can then combine with H 2 O 2 to generate peroxo–Ti species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential catalytic pathways are discussed as follows. Numerous studies have demonstrated that the Ti–peroxo species, formed by the combination of the Ti active site and H 2 O 2 , are responsible for the catalytic oxidation process. , As illustrated in the stacking diagram of the Ti 2 -SA cluster (Figure S5), a substantial number of Ti-OR units are extended outside rather than encapsulated by the calixarene. The labile −OR groups on the cluster surface can dissociate and expose the active Ti 4+ ions, which can then combine with H 2 O 2 to generate peroxo–Ti species.…”
Section: Resultsmentioning
confidence: 99%
“…15−21 They are multidentate-capable and versatile ligands, making them one of the most attractive options as protective ligands in TOCs. Recently, our group and others have investigated the coordination chemistry of calix[8]arene, 22−26 calix [4]arene, 27,28 and thiacalix [4]arene, 29,30 with Ti(IV), synthesizing a series of calixarene-stabilized TOCs with aesthetically appealing structures. These molecules display intriguing topologies, and their structures can be regulated by the addition of auxiliary ligands.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 For instance, a conical calix [4]arene or thiacalix [4] arene molecule tends to bind with titanium atoms via two to four phenolic oxygen atoms to form a shuttlecock-like secondary building unit (Scheme 1a-c). [19][20][21] A conical calix [6] arene molecule has two sets of three pendant phenolato oxygen atoms, each chelating a Ti ion, forming a bi-nuclear Ti 2 -C6A motif (Scheme 1e). 22,23 The calix [6]arene molecule with an inverted biconical configuration also provides two binding sites for titanium chelation, either endo-or exo-to the cavity.…”
Section: Introductionmentioning
confidence: 99%